Guía de actividades lúdicas para el desarrollo corporal de los niños y niñas de nivel inicial dos paralelo “A” de la unidad educativa José Antonio Eguiguren “La Salle” periodo septiembre 2013-julio 2014 - Matailo González, Ruth Elizabeth (2015)
This research work aims to establish the importance of leisure activities for the development of the body of the boys and girls of level two of the initial de la Unidad eductiva José Antonio Eguiguren "LA SALLE", thus improving the development of children through the game. In the Initial Education sets out the need to use the game as a fun learning tool because it provides the child and the girl the opportunity of the build your own concept through the process of assimilation and accommodation, it is necessary to use the game, the toys, the playful activity and the toy library, such as basic elements of the formal education process. For the process of research methods were used as: comprehensive, analytical, synthetic, participatory diagnosis, deductive, hermeneutical, dialectical, descriptive. Diagnosed in the Educational Unit José Antonio Eguiguren "LA SALLE" in the boys and girls of initial level two parallel "A" that there are some shortcomings such as: Lack of stimulation in the gross motor, low use of ludic activities on behalf of the teacher, lack of interest in parents to stimulate the child in the development of the body, difficulties in different areas of the development of the body such as: balance, coordination, and effectively the ludic activities through the game can be used as a method of education to improve the body's development of the child of initial level two.